HEARING DISABILITIES AND DIFFICULTIES IN EDUCATION: proposal for the development of smart furniture for a more inclusive education - Assis , Diego Edson de Assis; Francisco da Silva, Eunice Estevão; Del Vechio , Gustavo Henrique (Revista Interface Tecnológica, 2022)
In Brazil and in the world, deaf and hearing-impaired people face not only physical difficulties, but also social difficulties, that is, inclusion or accessibility. This perspective is not different in the educational field. Put in this way, this study seeks to understand the main difficulties imposed on disabled people, as well as on teachers, in relation to access and dissemination of knowledge in regular education, that is, in classrooms. Having understood these difficulties, it presents a proposal for the development of a product, referring to a line of school furniture that supports hardware and software and that can provide a more accessible environment for the disabled, so that they can participate in classrooms more inclusive and dynamic. What can be observed from this study is that there are still many barriers to be overcome in order to achieve a fuller and more accessible education for these individuals, however, the initiative to propose projects of this nature can be a hope for better access to education. knowledge for everyone, without distinction.
Keywords: Hearing impaired; deaf; Product development; Education; Social inclusion